CONSUMER PROTECTION AGAINST TRADED PIG MEAT IN COMMUNITY - Handoko, Panggung (International Journal of Law and Legal Ethics, 2022)
This study aims to determine consumer protection for the circulation of pork that is traded in deceit in society, by discussing the issue of whether the perpetrators can be sued if pork is sold as venison and how the government protects consumers who are harmed by consuming pork. The research using the statutory approach and the case approach, it is concluded that: The perpetrator can be sued if the pork sold is said to be venison. Selling venison when in fact it is pork, it can be said that the perpetrator has committed an act that violates consumer rights, namely for correct, clear, and honest information regarding the condition and guarantee of goods as stipulated in Article 4 letter c of Law no. 8 of 1999. Selling pork without including a label that the meat is not halal violates Article 8 paragraph (1) letter h of Law no. 8 of 1999, and the meat was sold to convince potential buyers, the perpetrator said that he was not honest or lying, with the intention of misleading the buyer to seek profit, that the meat being sold was venison, as an act of deception carried out by the perpetrator. The form of government protection for consumers who are harmed by consuming pork, that the government through the Minister of Health and the Minister of Trade and BPOM provide supervision over trade and circulation of goods as stipulated in Article 30 of Law no. 8 of 1999 as a repressive and preventive supervision. Against consumers who are harmed by violating consumer rights and trading goods without attaching a label as referred to in Article 4 letter c and Article 8 paragraph (1) letter h of Law no. 8 of 1999, as a violation of the law, the settlement is through a lawsuit to the General Court in the form of reimbursement of costs, losses (both material and immaterial) as stipulated in Article 1365 of the Civil Code.